Language Experience with a Native-Language Phoneme Sequence Modulates the Effects of Attention on Cortical Sensory Processing - Wagner, Monica; Lee, Jungmee; Mingino, Francesca; O'Brien, Colleen; Constantine, Adam; Shafer, Valerie L.; Steinschneider, Mitchell (Frontiers in Neuroscience, 2017)
Auditory evoked potentials (AEP) reflect spectro-temporal feature changes within the spoken word and are sufficiently reliable to probe deficits in auditory processing. The current research assessed whether attentional modulation would alter the morphology of these AEPs and whether native-language experience with phoneme sequences would influence the effects of attention. Native-English and native-Polish adults listened to nonsense word pairs that contained the phoneme sequence onsets /st/, /sət/, /pət/ that occur in both the Polish and English languages and the phoneme sequence onset /pt/ that occurs in the Polish language, but not the English language. Participants listened to word pairs within two experimental conditions designed to modulate attention. In one condition, participants listened to word pairs and performed a behavioral task to the second word in the pairs (“with task”) and in the alternate condition participants listened to word pairs without performing a task (“without task”). Conditions were counterbalanced so that half the English and Polish subjects performed the “without task” condition as the first testing session and the “with task” condition as the second testing session. The remaining English and Polish subjects performed the tasks in the reverse order. Two or more months separated the testing sessions. Task conditions did not modulate the morphology of the AEP. Attention, however, modulated the AEP by producing a negative shift in the overall waveform. This effect of attention was modulated by experience with a native-language phoneme sequence. Thus, only Polish listeners showed an effect of attention to the native language /pt/ onset when the behavioral task occurred as the second testing session for which attention demands were reduced. This effect began at 400 ms and suggests a mechanism at intermediate stages within auditory cortex that facilitates recognition of the native language for comprehension.